How good is controlled attenuation parameter and fatty liver index for assessing liver steatosis in general population: correlation with ultrasound - Carvalhana, S. (2014)
Liver steatosis measurement by controlled attenuation parameter (CAP) is a non-invasive method for diagnosing steatosis, based on transient elastography. Its usefulness as screening procedure for hepatic steatosis in general population has not been previously evaluated. The aim of this study was to evaluate the diagnostic accuracy of CAP and fatty liver index (FLI) for detection and quantification of steatosis in general population.